Analysis of radiation exposure effect on the development of non-tumoral morbidity in the persons evacuated in childhood and adolescence from the 30 km zone of the Chornobyl NPP - Prykashchykova, K.Ye.; Pavlovskyi, Ye.Ye.; Yaroshenko, Zh.S.; Kostiuk, H.V.; Gned, M.Ye.; Mykhailovskyi, Ye.L.; Solonovych, S.I.; Lukianiuk, V.O.; Oliper, O.V.; Syrovenko, V.I. (Environment & Health, 2017)
Objective: We studied the development of non-tumoral morbidity for the period of 1993-2012 in the adults evacuated in childhood and adolescence from the 30 km zone of the Chornobyl NPP depending on the doses of radiation exposure and gender. Materials and methods: We calculated the relative risk (RR) and its confidence interval (CI) at different values of small doses of external radiation exposure of the whole body (less than 0.05 Gy – the control group, 0.05 – 0.37 Gy) to find out the dependence of the development of non-tumoral morbidity in the cohort as a whole (3866 persons) on the age at the moment of the evacuation (children - 3024 persons, teenagers – 842 persons), gender and doses of radiation exposure. Results and conclusions: For the post-accidental period during 1993-2012 especially high risks of the development of cataract, the value of RR (CI) - 4.10 (3.92; 4.28), male genital diseases, female genital inflammatory diseases, diseases of mammary gland, iron-deficiency anemia, the value of RR (CI) - from 2.32 (2.22; 2.42) to 2.63(2.51; 2.75) were identified in the persons evacuated in adolescence in comparison with the persons evacuated in childhood. Significant relative risks were detected for thyroid diseases, white blood diseases, neurotic disorders, psychopathy and other psychotic disorders, disorders of non-psychotic character, hypertension, cerebrovascular diseases, gallbladder diseases, biliary tract and pancreas diseases, urinary system diseases, RR(CI) from 1.09 (1.04;. 1,14) to 1.85 (1.76; 1.93).